2005
DOI: 10.1097/01.blo.0000169081.61398.58
|View full text |Cite
|
Sign up to set email alerts
|

No Negative Effects of Bone Impaction Grafting with Bone and Ceramic Mixtures

Abstract: Reconstructing large loaded bone defects with ceramic bone graft extenders is tempting considering the expected future donor bone shortage. However, whether there are negative effects is unknown. Standardized large defects in the acetabulum of goats were created and subsequently reconstructed with metal mesh and impacted morselized cancellous bone grafts or a 50/50% volume mixture of tricalcium phosphate-hydroxyapatite granules and morselized cancellous bone grafts using the bone impaction grafting technique. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Furthermore, ovine and caprine studies have shown impaction grafting with BoneSave to be as least as good as allograft in the clinical setting with regard to function, radiographic analysis, and new bone formation (Arts et al 2005b, Blom et al 2005a). As the ceramic was mixed with allograft, it would not completely eliminate the risks of antigenicity and infection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ovine and caprine studies have shown impaction grafting with BoneSave to be as least as good as allograft in the clinical setting with regard to function, radiographic analysis, and new bone formation (Arts et al 2005b, Blom et al 2005a). As the ceramic was mixed with allograft, it would not completely eliminate the risks of antigenicity and infection.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, newly developed bone substitutes have been tested in vivo using numerous experimental models, most of them involving larger animals such as dogs,16 goats,17 or rabbits 18. In our study, we have used the dorsal skinfold chamber model of Syrian golden hamsters, which bears the advantages of convenient handling and lower costs.…”
Section: Discussionmentioning
confidence: 99%
“…66 Graft incorporation of tricalcium phosphate/HA particles has been observed in a goat model of contained acetabular deficiencies reconstructed with a 50/50 mixture of cancellous bone and tricalcium phosphate/HA granules. 67 Although the mechanical stability may be improved with these extenders, the biological aspects of the graft incorporation and remodelling have yet to be fully studied. A denser graft may reduce cement penetration and also reduce ingrowth and lead to greater failure.…”
Section: Bone Graft Extendersmentioning
confidence: 99%
“…Histological retrieval analysis has confirmed that remodelling does occur with gradual but variable ingrowth. [67][68][69][70][71] Studies using positron emission tomography have shown that the initial increase in blood flow and bone remodelling following surgery reduces to baseline levels by one year, implying that incorporation is complete by this stage. 72 However, an appraisal of bone incorporation employing bone scintigraphy reported that the uptake became normal two to three years after surgery, demonstrating that slower remodelling continues for a considerably longer period.…”
Section: Graft Incorporationmentioning
confidence: 99%